Effect of Nursing Training on Improving Knowledge, Skills, and Attitudes of Clinical Nurses - I Ketut Sudiarta; Emiliana Tarigan; Sudibyo Supardi (Universitas Triatma Mulya, 2019)
Introduction. Clinical nurses are competent with good knowledge, skills and attitudes. These efforts are carried out through integrated training adaptation of the concept of Patricia Benner's From Novice to Expert . The study aims to determine the effect of nursing training on increasing knowledge, skills and attitudes. Methods. This research is a quantitative research with a quasy experiment design, using a non-randomized control group pretest and posttest design. The research sample amounted to 100 people, divided into two groups, namely the intervention and control groups with the same number. The study was conducted for 12 weeks. Results. The results of bivariate analysis with a mean score of posttest 97.20, increased 21.6%, knowledge was statistically significant with p = 0.000. the posttest skills average score was 92.96, increased by 23.92%, the skills were statistically significant with p = 0.000 and posttest 50.06 attitude average, increased by 6.44%, statistically significant with p = 0.000, there was the influence of nursing training on increasing clinical nurses' knowledge, skills and attitudes . The results of the multivariate analysis of nursing training were statistically significant for the increase in clinical nurses' knowledge (p = 0.000), having the possibility of knowledge increasing 10 times, increasing skills statistically meaningful (p = 0.000), having the possibility of skills increasing by 1.4 times and statistically significant attitudes (p = 0.000), has the possibility of an increase in attitude 0.8 times compared to not getting training, no confounding variables are affected. Conclusion. Knowledge, skills and attitudes are influenced by nursing training from material aspects, methods, facilities, instructors and post-training evaluation methods. Thus to achieve the optimal quality of knowledge, skills and attitudes, it is recommended to provide assistance, supervision, assistance and guidance in an integrated manner.